An investigation of general predictors for cognitive–behavioural therapy outcome for anxiety disorders in a routine clinical setting. Issue 3 (25th March 2016) - Nielsen, Sara Kerstine Kaya; Vangkilde, Signe; Wolitzky-Taylor, Kate B; Daniel, Sarah Ingrid Franksdatter; Hageman, Ida
Abstract : Introduction: Cognitive–behavioural therapy (CBT) is effective for treating anxiety disorders and is offered in most mental health services around the world. However, a relatively large number of patients with anxiety disorders do not benefit from CBT, experience relapses or drop out. Reliable predictors of treatment effects are lacking. The aim of this study is to investigate the predictive value of emotion regulation and attentional control for CBT outcome in a routine setting. Methods and analysis: In this prospective and practice-based study, 112 patients with anxiety disorders referred for manual-based group CBT at two psychiatric outpatient clinics will be recruited. Emotion regulation, severity of anxiety and attentional control will be assessed with self-report measures and with an experimental computer-based attentional control task at baseline, post-treatment and at a 6-month follow-up. Emotion regulation will be measured with Difficulties in Emotion Regulation Questionnaire, severity of anxiety will be assessed with Beck Anxiety Inventory and attentional control will be measured with the self-report questionnaire, Attention Control Scale, and with an experimental computer-based attentional control task based on theory of visual attention. Data will be analysed using multilevel mixed-effects modelling. Ethics and dissemination: The study is approved by the Danish National Ethical Board, the Department of Psychology Ethical Board, University of Copenhagen and by the Danish Data Protection Agency. Study findings will be disseminated through peer-reviewed journal publications and conference presentations. The Danish Committee System on Health Research Ethics has been notified about the project. Trial registration number: NCT02638363.